Estimation of oxygen tension in retinal capillaries from phosphorescence lifetime images - Yildirim, Isa; Ansari, Rashid; Wanek, Justin; Yetik, Imam Samil; Shahidi, Mahnaz (IEEE, 2009)
Investigating the effect of retinal oxygenation abnormalities in the development of common eye diseases requires accurate assessment of oxygen tension in retinal vasculatures. Estimation of oxygen tension in retinal capillaries using phosphorescence lifetime imaging is addressed in this paper. Separation from tissue and oxygen tension estimation is a more challenging task for capillaries when compared with large retinal vessels due to the finer structure and noise predominance in capillaries. An automated segmentation procedure is applied using the EM algorithm and noise contamination is reduced using a regularization method unlike previous approaches to capillary analysis where segmentation was done manually and noise contamination was ignored. We demonstrate the effectiveness of the proposed method by applying it to the retinal image data acquired from rat eyes, and we show that the oxygen tension estimate of retinal capillaries falls in the physiologically expected range.